Foreign Language for Students of Higher Education Institutions Important Tasks of Teaching - Tashxodjayeva Patima Bakiyevna (Zien Journals, 2023)
This article analyzes the important tasks of teaching foreign languages to students of higher educational institutions and the issues of their application in a number of projects related to the implementation of Russian language teaching concepts in the framework of international medical relations in the formation of students' communicative competence in the Russian language during the educational process.
Keywords: integrated; non-philological; communicative competence; language literacy